قواعد قرآنية في مواجهة الأزمات: جائحة كوفيد-19 أنموذجا - اللهو، مشاعل أنور يوسف; العنزي، مها محمد رومي (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2020)
يتناول هذا البحث مجموعة من القواعد القرآنية المتعلقة بمواجهة الأزمات، وربطها بالواقع من خلال جائحة كوفيد ١٩، وذلك بهدف الكشف عن هدايات القرآن الكريم وربط المسلمين بهذا الكتاب العظيم الذي تشتد الحاجة إليه في الأزمات، وقد اعتمد البحث على المنهج الاستقرائي -شبه التام- من خلال استقراء مجموعة من الآيات القرآنية ذات الصلة بموضوع الدراسة، واستقراء ما كتبه العلماء والمفسرون حولها، والمنهج التحليلي من خلال تحليل الآيات القرآنية، وما تضمنته من دلالات لغوية وبلاغية، وما كتبه العلماء والمفسرون حولها لاستنباط أهم القواعد القرآنية المتعلقة بالموضوع، وربطها بالواقع. وقد تناول البحث قواعد مهمة متعلقة بالبناء الإيماني والفكري والنفسي في القرآن، ومسؤولية القيادة الحكيمة في تجاوز الأزمات، وقواعد التعامل مع الأخبار والمعلومات المتعلقة بالأزمات.
The research at hand displays a group of Qur'anic tips regarding the methodology of facing crises as well as observing the reality of COVID-19 pandemic in order to reveal the great guidance of the Holy Qur'an and draw Muslims' attention to this great book to which they always resort in time of need and crisis. The research is run, to a large extent, in accordance with the inductive approach. It investigates a group of Qur'anic verses of relevance to the topic of this study as well as exploring what the scholars and interpreters have written regarding such issues. In addition, the research applies the analytical approach through analyzing the content of the Qur'anic verses; semantically and rhetorically on parallel lines with what scholars and interpreters have written regarding such verses. Accordingly, the researchers would be able to deduct the most important Qur'anic tips related to both the topic and reality. Moreover, the research has handled an issue of importance to the faithful, intellectual and psychological structure in the Holy Qur'an. It has also highlighted the responsibility of the wise leadership to come over crises. Finally, the research has also handled the rules of processing news and information concerned with crises.
Keywords: التربية الإسلامية -- إدارة الإزمات -- فيروس كورونا "كوفيد-19" -- القرآن الكريم